The Post-Cold War developments, energy resources and the US position in the new era "a literature review" - Naji, Saeid; Jawan, Jayum (Canadian Academy of Oriental and Occidental Culture, 2011)
With the end of the cold war and collapse of the Eastern superpower, it is significant to study the position of great countries particularly the United States in the geopolitical world order. It also is very important to identify important geoeconomic factors which are effective in the formation of the relations among the great powers in the new era. The role of energy has always been determined as a significant factor in the global developments as well as in the activities of powerful states especially the US. This paper reviews some proper studies to establish logical relation between energy resources and position of the US in the geopolitical world order. The following studies refer to decline of US hegemon especially in the late of 1960s and the US efforts to gain highest position in the world system. In these studies have been stressed on the oil reserves as a vital interest and it has been identified as main goal of the US presence in the Persian Gulf region. Here also has been stressed on the domination of geo-economic logic over geopolitical logic in the US international policies.